2018
DOI: 10.1016/j.lfs.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Understanding lamin proteins and their roles in aging and cardiovascular diseases

Abstract: The occurrence of cardiovascular diseases increases with age independent of other risk factors, and the percentage of senescent cells is significantly elevated in vascular cells at atherosclerotic sites. Patients with accelerated aging syndromes caused by mutant lamin A protein, a structural component in nuclear lamina, also share many similarities with normal aged people, including the propensity to develop atherosclerosis. Recent studies have revealed the accumulation of prelamin A in normal aged vascular ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 211 publications
1
6
0
Order By: Relevance
“…Since Klotho has the kidney defence ability (Morales et al 1996, for example) it should promote chronic renal illness through improper tissue healing and poor damage protection. The elevated amount of casapase 14, a protein that is implicated in apoptosis and prelamin A/C in CF exosomes, as accumulation of lamina proteins in different neurodegenerative illnesses (Jiang & Ji 2018), also suggests this "accelerated ageing" problem (Le Dour et al, 2017). Our findings also demonstrated that proteins and gene sets in urine exosomal matrisomes were consistently downregulated.…”
Section: Tissue Repair Dysregulation and A Potential Pro-aging Cf Dis...supporting
confidence: 55%
“…Since Klotho has the kidney defence ability (Morales et al 1996, for example) it should promote chronic renal illness through improper tissue healing and poor damage protection. The elevated amount of casapase 14, a protein that is implicated in apoptosis and prelamin A/C in CF exosomes, as accumulation of lamina proteins in different neurodegenerative illnesses (Jiang & Ji 2018), also suggests this "accelerated ageing" problem (Le Dour et al, 2017). Our findings also demonstrated that proteins and gene sets in urine exosomal matrisomes were consistently downregulated.…”
Section: Tissue Repair Dysregulation and A Potential Pro-aging Cf Dis...supporting
confidence: 55%
“…As Klotho is involved in the kidney's ability to defend against renal insults [5], this defect should favor chronic kidney disease by abnormal tissue repair and defective protection against damage. This "accelerated aging" defect is also suggested by the increased level of caspase 14, a protein involved in apoptosis and of prelamin A/C in CF exosome, as accumulation of lamin proteins, are involved in various neurodegenerative diseases [28,29].…”
Section: Dysregulated Tissue Repair and Potential Pro-aging Cf Diseasmentioning
confidence: 95%
“…The complexity of atherosclerosis involves many factors in addition to prelamin A in VSMC, foam cells, and endothelial cells as described in many articles [45,53,54]. The review of the role of lamins in atherosclerosis by Jiang and Ji provides additional useful information [55]. AGING…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%